QUALITY OF SEDIMENTARY ENVIRONMENT IN NAI LAGOON, NINH THUAN PROVINCE - Vinh, Lê Thị (Vietnam Journal of Marine Science and Technology, 2014)
The paper represents some aspects on the quality of the sedimentary environment in Nai lagoon. Results performed in May, 2011 shows that the contents of the organic materials and heavy metals in the sediment were considerably various ( Corg.: 0.08 - 1.44%,  Norg: 505.3 - 1279.0 μg/g,  Pt: 349.0 - 834.2 μg/g; Zn: 5.2 - 49.9 μg/g; Cd: 0.12 - 0.5 μg/g, Cu: 0.8 - 11.1 μg/g, Pb:13.7 - 21.1 μg/g, Fe: 3,066 - 15,999 μg/g, Cr: 3.5 - 23.4 μg/g and Mn: 57.9 - 352 μg/g). Overall, content of  Corg. and heavy metals decreased from the top toward the mouth of lagoon, while N and P were highest in the middle area and mouth of lagoon. The most part of the organic matters in the top of lagoon are terrigeneous in origin particularly, while those in mouth are mainly from human activities. Generally, the sedimentary environment in Nai lagoon, in term of organic materials and heavy metals, was suitable for the aquatic life. However, from 1995 to now, there have been the increasing trend in organic matter (N and P) and heavy metal contents and the decreasing trend in  Corg.